Ferrocement Composites for Strengthening of Existing School Structures in Albania - Guri, Merita; Vesho, Nikolla; Marku, Aguljeln (International Journal of Scientific Research in Civil Engineering, 2020)
The study includes analyses of existing school structures built with retaining unreinforced masonry, where some structural problems have been identified as a result of the degradation of masonry parameters over the years, which reduce their carrying capacity. In Albania, as a high seismic risk country, it is very important to design and evaluate anti seismic structures. From the economic point of view, there are two possibilities: their reinforcement or collapse to replace them with new structures. The possibility of choice is given to us after assessing their current situation and performance. The new and old Albanian design codes do not have established procedures for their seismic evaluation. For this reason, it is necessary to evaluate and improve the carrying capacity of these school structures projects selected in Tirana which are designed in accordance with the old codes [KTP-78, 1978; KTP-89, 1989], nowadays based on the calculation of structural Eurocodes such as EN1996, with ETABS V15.9 software. Ferrocement is a low-cost material that improves resistance, stiffness and ductility for masonry school structures. The study provides recommendations and results for the application of this reinforcement technique to similar traditional techniques applied in our country and Balkan region.
Keywords: URM-buildings; Seismic Performance; Stress; Strain Investigation; Stiffness; Ductility